Investigação do potencial antiepiléptico de um óleo de extrato de Cannabis sativa rico em canabidiol: uma abordagem in sílico e in vivo - Santos, Aline Matilde Ferreira dos (2023)
Epilepsy is one of the most common brain diseases, affecting about 2% of the Brazilian population and approximately 50 million people worldwide. Although there is already a considerable number of antiepileptic drugs on the market, there is a need for new drugs, mainly to reduce refractoriness to treatments. In the search for new pharmacological therapies are the substances found in Cannabis sativa. Thus, this work aimed to evaluate the effect of Cannabis sativa rich in CBD (OERCBD) in silico and in vivo. Previously, phytochemical analysis was performed to identify the primary components of OERCBD, followed by molecular docking to evaluate the interaction of these molecules and their ligands. The in vivo studies used male Swiss albino mice (Mus musculus), around 3 months old, which were submitted to behavioral pharmacological screening protocols and determination of LD50 (n=3), induction of seizures by intraperitoneal injection (i.p) of pentylenetetrazole (PTZ, 75mg/kg) (n=8), and the maximum atrial electroshock (MES) model (n=8) with acute or repeated doses administration of OERCBD for 14 days. The animals were divided into a control group, which received olive oil (AZT), groups treated with OERCBD at doses of 15, 30 and 60mg/kg (v.o) and diazepam (DZP, 4mg/kg i.p) in the PTZ test, or phenytoin (FEN, 30mg/kg i.p) in the MES. For the statistical analysis of the induced epileptic seizure tests, the Shapiro-Wilk and Bartlett tests were performed to determine that all parameters should be analyzed using non-parametric tests, followed by the Kruskal-Wallis test and the Dunn test. For the statistical analysis of the percentage of mortality/survival, Fisher's exact test was used, p values <0.05 were considered statistically significant. As a result, gas chromatography-mass spectrometry (GC-MS) identified CBD as the primary component of OERCBD. The molecular docking study demonstrated a good interaction between CBD and the GABAA receptor, but even better with NaV channels. In acute toxicity and LD50, the dose of 300mg/kg (v.o) showed signs of irritability and sedation, while in the doses defined for the treatment (15, 30 and 60mg/kg) such effects were not observed. In the PTZ test, OERCBD in the three doses was not able to increase the latency time for myoclonic and tonic-clonic epileptic seizures, prevent or decrease the severity of the seizures, but protected the animals from the occurrence of death when compared to the group AZT. In MES, the three doses of OERCBD both in acute and repeated doses administration were not able to reduce the duration of tonic epileptic seizures with the extension of the limbs, nor the latency for posture recovery, but in acute administration, there was a reduction in the occurrence of deaths, especially in the highest doses. In the repeated doses administration, there was a worsening in this parameter, mainly in the lowest dose. The in vivo results demonstrate that although there is a good interaction between CBD and GABAA receptors and NaV sodium channels, this may not be enough, reflecting the need for coadministration with other antiepileptic drugs, as already recommended in the clinic. However, the results contribute to understanding the complex brain response to phytocannabinoids and highlight the importance of further investigations to determine your potential pharmacological responses.